B-type natriuretic peptide levels and volume status in twice-weekly hemodialysis patients. Issue 1 (1st January 2021) - Fang, Nina; Che, Miaolin; Shi, Ling; Yu, Zanzhe; Ni, Zhaohui; Fang, Wei; Pang, Huihua; Gu, Leyi; Lin, Xinghui
Abstract: Background: Twice-weekly hemodialysis (HD) could be regarded as an important part of incremental hemodialysis, volume status of this treatment model remains to be elucidated. Methods: Patients undergoing regular twice-weekly or thrice-weekly hemodialysis in our unit on June 2015 were enrolled into the cohort study with an average of 2.02 years follow-up. Volume status of the subjects was evaluated by clinical characteristics, plasma B-type natriuretic peptide (BNP) levels and bioimpedance assessments with body composition monitor (BCM). Cox proportional hazards models and Kaplan–Meier analysis were used to compare patient survival between the two groups. Results: Compared with patients on thrice-weekly HD, twice-weekly HD patients had significantly higher log-transformed BNP levels (2.54 ± 0.41 vs. 2.33 ± 0.49 pg/ml, p  = 0.010). Overhydration (OH) and the ratio of overhydration to extracellular water (OH/ECW) in twice-weekly HD group were significantly higher than that of thrice-weekly HD (OH, 2.54 ± 1.42 vs. 1.88 ± 1.46, p  = 0.033; OH/ECW, 0.17 ± 0.07 vs. 0.12 ± 0.08, p  = 0.015). However, subgroup analysis of patients within 6 years HD vintage indicated that the two groups had similar hydration status. Multivariate Cox regression analysis showed that log-transformed BNP levels, serum albumin and diabetes status were predictors of mortality in hemodialysis patients. Kaplan–Meier survival analysis indicated that patients with BNP levels higher than 500 pg/ml had significantly worse survival compared with those with lower BNP levels ( p  = 0.014). Conclusions: Twice-weekly hemodialysis patients had worse volume status than that of thrice-weekly HD patients especially for those with long-term dialysis vintage, BNP level was a powerful predictor of mortality in HD patients.